Domestic animal behavior for veterinarians and animal scientists - Houpt, Katherine A. (Wiley-Blackwell, 2011)
Domestic Animal Behavior, Fifth Edition is a fully updated revision of this classic text, with chapters examining key behavior issues ranging from communication to social structure. Coverage encompasses a wide variety of domestic animals including cats, dogs, horses, pigs, sheep, and cattle